P300 involvement in apoptosis and metastasis in triple negative breast carcinoma (TNBC) - Gallardo, Guillermina Ana (2020)
Triple-negative breast cancer (TNBC) is a heterogeneous group of tumors that lack specific molecular targets. Therefore, it is neces- sary to investigate potential tumor markers for this subtype of BC. There are few studies in TNBC on the role of p300 in apoptosis and they are contradictory. Previously, we published that pharma- cological inhibition of p300 increases apoptosis in murine BC cells, however, it is necessary to check whether the same effect occurs in human TNBC cells. Recently a prometastatic role of p300 in BC has been found. In addition, we demonstrated that pharmacological inhi- bition of p300 decreases migration and adhesion in TNBC, showing the need to delve into the molecules involved. Hence, the aim of this work was to study the effect of the inhibition of the acetylase func- tion of p300 in the processes of apoptosis and metastasis in human TNBC cells. The MDA-MB-231 cell line was treated with VV59 (in- hibitor of the acetylase function of p300) or its vehicle (DMSO). In a cell viability assay, we observed that the pharmacological inhibition of p300 produced a decrease in the number of cells compared to vehicle (p<0.001). When we analyzed the cell cycle by flow cytome- try, we detected an increase in the sub G0 phase and a decrease in the G0/G1 phase in the cells treated with VV59 compared to those treated with the vehicle (p˂0.001). We also observed an increase in apoptotic morphology in VV59-treated-cells compared to vehi- cle-treated cells by dapi staining (p˂0.001). On the other hand, by immunofluorescence assay we detected that pharmacological inhi- bition of p300 induced an increase in the levels of E-cadherin and β-catenin in the membrane, and a decrease in the number of stress fibers compared with the control cells (p˂0.01). Taken together, these results demonstrate an antitumor role for pharmacological inhibition of p300 acetylase function in TNBC.